Depth Estimation of Potential Field by Using a New Downward Continuation Based on the Continued Fraction in Space Domain - Wenna Zhou; Chong Zhang; Dailei Zhang (Earth and Space Science, 2021)
Abstract Depth estimation of potential field data is a powerful tool for geologic source interpretation. It can be implemented by using downward continuation method based on a normalized algorithm. However, when several geological bodies with different burial depths exist in the research area, the calculated depth usually tends to be the average depth. To overcome this limitation, we proposed a new downward continuation method based on the relationship between the Taylor series and the continued fraction in space domain. Theoretically, it can obtain the singular (quasi‐singular) source point directly, which indicates the position of source. In practical applications, we only need to calculate downward continuation data from the original level to an expected maximum depth. The absolute value is calculated so that the maximum value indicates the source depth range. We used different synthetic models to test our method and obtained satisfactory results. The advantages of depth estimation using the new method were illustrated by comparing it with the normalized total gradient method. Finally, we applied the new method to field data, and results were in agreement with the previous results. This illustrated that the new method can be used for high resolution, high accuracy depth estimation.